Analisis Pesan, Tanda Verbal dan Visual Kajian Semiotik Pada Iklan Santé Publique France MangerBouger - Risalah Azzahriwan; Dadang Sunendar; Rika Widawati (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to examine the meaning of messages in one of the public service advertisements MangerBouger produced by Santé Publique France using Roland Barthes’ semiotic approach. Advertising, as a medium of public communication, not only conveys messages directly but also shapes awareness through the use of visual and verbal signs rich in cultural and ideological meanings. This research employs a descriptive qualitative method focusing on in-depth interpretation of meaning within social phenomena in the context of visual communication. The research object is the MangerBouger advertisement entitled “Commencez par Manger des Légumes Secs un Peu Plus Souvent”, obtained from the YouTube platform, and analyzed through visual observation, literature review, and documentation. The data were analyzed by dissecting the layers of denotative, connotative, and mythical meanings based on Barthes’ theory. The results show that the advertisement delivers health messages in a symbolic and persuasive way, and constructs a certain cultural representation that appears natural. Barthes’ semiotic approach proves effective in revealing hidden meanings behind the visual and verbal representations used in public communication strategies by French government agencies.